Knowledge, attitudes and behaviors on antimicrobial resistance among general public across 14 member states in the WHO European region: results from a cross-sectional survey - Singh-Phulgenda, Sauman; Antoniou, Pantelis; Wong, Danilo Lo Fo; Iwamoto, Kotoji; Kandelaki, Ketevan (Frontiers in Public Health, 2023)
Background Antimicrobial resistance (AMR) is a major global public health threat requiring urgent action. Pan-European data on knowledge, attitudes and behaviors among the general public regarding antibiotic use and AMR is limited. Methods A multicentric, cross-sectional survey of the general public was conducted in the capital cities of 14 Member States of the WHO European Region. A validated questionnaire from the AMR Eurobarometer survey was used to collect data on antibiotic use and knowledge, access to antibiotics, and understanding of policy responses through face-to-face exit interviews. Results Out of 8,221 respondents from 14 Member States, 50% took antibiotics in the past 12 months and the majority (53%) obtained their most recent course from a medical practitioner. The most reported reasons for taking antibiotics orally in the past 12 months were cold (24%), sore throat (21%), cough (18%), and flu (16%). Overall, 84% of participants showed a lack of knowledge about appropriate antibiotic use. However, only 37% of respondents reported receiving any information in the past year about the importance of avoiding unnecessary antibiotic use. Doctors were the most cited (50%) and most trusted (80%) source of information. Among respondents who experienced COVID-19, 28% took antibiotics with a prescription, while 8% took antibiotics without a prescription. Conclusion This study highlights the urgent need for targeted awareness campaigns and educational initiatives to address knowledge gaps and promote responsible antibiotic use. The findings emphasize the role of the general population in combating AMR. The data serve as baseline information for future evaluations and interventions in the Region.